PENINGKATAN KESADARAN DAN PARTISIPASI SISWA DALAM 3R UNTUK SEKOLAH DASAR HIJAU DAN BERSIH - Sibi, Paula Jessica Claudia; Fransisca Iriani R. Dewi; Fidiyah Anggini Oktavia Nababan; Celine Vandea Anika Tumundo (Jurnal Serina Abdimas, 2025)
SDN Maleber faces environmental challenges, including poor cleanliness, limited green spaces, and low participation from the school community in maintaining the environment. This community service program aims to improve students’ environmental awareness and behavior through a series of structured and participatory activities. The methods employed include initial observation, a pre-test using the Littering Attitude Scale (LAS), socialization and education on the 3R principles (Reduce, Reuse, Recycle), educational video screenings, hands-on practice recycling plastic bottles into flower pots, planting ornamental plants, and a post-test to measure changes in students’ attitudes. All activities actively involved third and fourth-grade students, supported by teachers and school staff. The results showed high enthusiasm, effective teamwork, and increased knowledge and skills among students regarding cleanliness and greening. Although there was no statistically significant change between pre-test and post-test scores, students’ understanding of cleanliness and greening remained stable, and the foundation for an environmentally conscious culture began to form within the school. This program underscores the importance of hands-on and collaborative learning in building environmental awareness and character. Moving forward, program sustainability and broader involvement of the entire school community and surrounding society are needed to achieve optimal changes in environmental behavior and knowledge. SDN Maleber menghadapi masalah lingkungan berupa kurangnya kebersihan, minimnya ruang hijau, dan rendahnya partisipasi warga sekolah dalam menjaga lingkungan. Program pengabdian masyarakat ini bertujuan meningkatkan kesadaran dan perilaku peduli lingkungan siswa melalui serangkaian kegiatan terstruktur dan partisipatif. Metode yang digunakan meliputi observasi awal, pre-test menggunakan Littering Attitude Scale (LAS), sosialisasi dan edukasi prinsip 3R (Reduce, Reuse, Recycle), pemutaran video edukasi, praktik langsung mendaur ulang botol plastik menjadi pot bunga, penanaman tanaman hias, serta post-test untuk mengukur perubahan sikap siswa. Seluruh kegiatan melibatkan siswa kelas 3 dan 4 secara aktif, dengan dukungan guru dan pihak sekolah. Hasil pelaksanaan menunjukkan antusiasme tinggi, kerja sama dalam kelompok, serta peningkatan pengetahuan dan keterampilan siswa terkait kebersihan dan penghijauan. Meskipun tidak terdapat perubahan signifikan secara statistik antara nilai pre-test dan post-test, pemahaman siswa tentang kebersihan dan penghijauan tetap stabil, serta mulai terbentuk fondasi budaya peduli lingkungan di sekolah. Program ini menegaskan pentingnya pembelajaran berbasis praktik langsung dan kolaboratif untuk membangun karakter peduli lingkungan. Ke depan, diperlukan keberlanjutan program dan keterlibatan lebih luas dari seluruh warga sekolah dan masyarakat sekitar agar perubahan perilaku dan pengetahuan lingkungan dapat terwujud secara optimal.